Triacontanol Reduces Transplanting Shock in Machine-Transplanted Rice by Improving the Growth and Antioxidant Systems - Li, Xiaochun; Zhong, Qiuyi; Li, Yuxiang; Li, Ganghua; Ding, Yanfeng; Wang, Shaohua; Liu, Zhenghui; Tang, She; Ding, Chengqiang; Chen, Lin (Frontiers in Plant Science, 2016)
Machine transplantation results in serious transplant shock in seedlings and results in a longer recover stage，which negatively impacts the growth of low-position tillers and the yield of machine-transplanted rice. A barrel experiment was conducted to examine the effect of the foliar application of triacontanol (TRIA) on machine-transplanted rice during the recovery stage. TRIA (0, 1, 5 and 10 µM) was sprayed over leaves two days before transplanting. The chlorophyll content, sucrose content, oxidative damage, antioxidant enzyme levels, glutathione (GSH) and ascorbate (ASA) redox states, tiller dynamics and yield components of the plants were investigated. The results show that foliar-applied TRIA significantly alleviates the growth inhibition and oxidative damage caused by transplant shock. Furthermore, the application of TRIA increased the chlorophyll and sucrose contents of the plants. Importantly, TRIA not only significantly improved the activity of catalase (CAT) and guaiacol peroxidase (POD), demonstrating that POD can play an important role in scavenging H2O2 during the recovery stage, but it also enhanced the redox states of ASA and GSH by regulating the activities of enzymes involved in the ASA-GSH cycle, such as ascorbate peroxidase (APX) and glutathione reductase (GR). A dose of 10 µM TRIA was the most efficient in reducing the negative effects of transplant shock, increasing the panicles, grain filling and grain yield per hill by 17.80%, 5.86% and 16.49%, respectively. These results suggest that TRIA acts to reduce transplant shock in association with the regulation of the redox states of ASA and GSH and antioxidant enzymes and serves as an effective antioxidant to maintain photosynthetic capacity and promote the occurrence of low tillers.